The Medical Research Council (UK)/Uganda Virus Research Institute Uganda Research Unit on AIDS – ‘25 years of research through partnerships’ - Kaleebu, P; Kamali, A; Seeley, J; .Elliott. A. M; Katongole‐Mbidde, E. (Wiley Subscription Services, Inc, 2014)
For the past 25 years, the Medical Research Council/Uganda Virus Research Institute Uganda Research Unit on AIDS has conducted research on HIV-1, coinfections and, more recently, on non-communicable diseases. Working with various partners, the research findings of the Unit have contributed to the understanding and control of the HIV epidemic both in Uganda and globally, and informed the future development of biomedical HIV interventions, health policy and practice. In this report, as we celebrate our silver jubilee, we describe some of these achievements and the Unit's multidisciplinary approach to research. We also discuss the future direction of the Unit; an exemplar of a partnership that has been largely funded from the north but led in the south.
Keywords: HIV, AIDS, Uganda, Medical Research Council/Uganda Virus Research Institute,coinfections, research, multidisciplinar